Cochrane Database of Systematic Reviews 2007
DOI: 10.1002/14651858.cd005261.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular treatment for ruptured abdominal aortic aneurysm

Abstract: New search run. One new study included. No new studies excluded. Text updated to reflect current Cochrane standards. 'Summary of findings' table added. No change to conclusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 83 publications
0
21
0
Order By: Relevance
“…The option of repair under local anesthesia provided by EVAR potentially compounds this benefit. 6,7 A recently published, large retrospective study of high-risk patients receiving care at the Veterans Affairs Administration who underwent EVAR for elective AAA repair cites a significantly lower 30-day and 1-year mortality in these patients. 14 These benefits of EVAR are also demonstrated in patients presenting with rAAA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The option of repair under local anesthesia provided by EVAR potentially compounds this benefit. 6,7 A recently published, large retrospective study of high-risk patients receiving care at the Veterans Affairs Administration who underwent EVAR for elective AAA repair cites a significantly lower 30-day and 1-year mortality in these patients. 14 These benefits of EVAR are also demonstrated in patients presenting with rAAA.…”
Section: Discussionmentioning
confidence: 99%
“…6 Several case reports and case series have demonstrated acceptable outcomes with EVAR for rAAA, 7-10 but most are small, retrospective, and limited by the lack of a valid control group. In addition, these may represent a highly selective set of results from large-volume expert centers and may not be truly representative of all centers.…”
mentioning
confidence: 99%
“…When this trial was first discussed, observational studies (synthesised in systematic reviews [11][12][13][14] were reporting much lower 30-day mortality for endovascular repair of ruptured AAAs and some such studies 11 have suggested that this should become the new gold standard treatment of ruptured aneurysms without the need for a randomised trial. In addition, the in-hospital and 1-year costs of treating ruptured aneurysms by endovascular repair may be up to 40% lower than for treatment by open repair.…”
Section: Chapter 1 Introductionmentioning
confidence: 99%
“…3 This might be due to the combined effects of general anesthesia, surgical exposure, hemorrhage, and aortic clamping with lower torso ischemia-reperfusion injury. 7 In 1991, Parodi et al 8 introduced a minimally invasive technique for AAA repair. This endovascular aneurysm repair (EVAR) 8 can be performed under local anesthesia with less blood loss and no need for aortic cross-clamping.…”
mentioning
confidence: 99%
“…As a result of lack of randomization, comparative studies so far are flawed by methodologic inadequacies such as selection bias, which is created by inadequate control of potential confounding secondary to inadequate patient matching. 7 Patients who are selected for rEVAR constitute a lower-risk category, presumably because they need to be hemodynamically more stable for preoperative imaging and have a more favorable anatomic configuration.…”
mentioning
confidence: 99%